The Practice of Buying and Selling Black Market Goods on The Perspective of Islamic Economic Law - Khairudin (NUSANTARA: Journal Of Law Studies, 2022)
The purpose of this study is (1) to reveal how the practice of buying and selling black markets in Ratu Samban District, Bengkulu City. (2) To analyze the review of Islamic economic law on the practice of buying and selling black markets in Ratu Samban District, Bengkulu City. The research method used is a qualitative approach and this type of research is field research. The informant in this study was the seller and consumer. The results of this study revealed that: (1) The practice of buying and selling black markets in Ratu Samban Subdistrict, Bengkulu City, namely, the lack of openness of the seller regarding information on goods sold. For the buying and selling process the same as buying and selling mobile phones in general, where there is a bid process, checking goods, and the payment stage. For the quality of goods is very different from the original version, the difference can be seen through packaging boxes, physical mobile phones, IMEI, and processors. (2) The review of Islamic economic law to buying and selling black market mobile phones, namely: The sale and purchase is included in the sale and purchase that is forbidden in Islam, where this buying and selling contains elements of unclear and incomplete information about the goods sold.